2022
DOI: 10.1108/mmms-12-2021-0203
|View full text |Cite
|
Sign up to set email alerts
|

Breaking process of composite membranes used in desalination phenomenon

Abstract: PurposeThe purpose of this paper is to present a study of the breaking process of composite membranes used in the water desalination. Temperature, fluid pressure and accumulate retained fluid are remarkable parameters, which are likely to damage these membranes.Design/methodology/approachIn this paper, the authors adopt the dynamics of a fiber bundle model to investigate the breaking process of composite membranes with fibres distributed parallel to the direction of fluid flow. The model is based on the fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Not only that but solar photovoltaics (SPV) can also solve the world's shortage of freshwater resources. Although composite mem-brane technology has been widely used in the field of seawater desalination, its performance is still affected by many factors [5][6][7], and PV integration technology is expected to improve the efficiency of reverse osmosis desalination [8]. Clearly, SPV is starting to play an important role in various industries.…”
Section: Introductionmentioning
confidence: 99%
“…Not only that but solar photovoltaics (SPV) can also solve the world's shortage of freshwater resources. Although composite mem-brane technology has been widely used in the field of seawater desalination, its performance is still affected by many factors [5][6][7], and PV integration technology is expected to improve the efficiency of reverse osmosis desalination [8]. Clearly, SPV is starting to play an important role in various industries.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, some important works ( Javaherdeh and Ashorynejad, 2014 ; Malvandi et al, 2014 ; Sheikholeslami and Ganji, 2015 ; Kasmani et al, 2016 ; Madaki et al, 2016 ; Salama, 2016 ; Akram et al, 2020 ) have reported on the flow over the wedge moving in the second-grade nanofluid, highlighting the impacts of the Cu–water combination of nanofluids over a mobile wedge, the homotopy asymptotic technique for the Falkner–Skan flow problem. The fluid transport in composite membranes used in water desalination is presented in recent articles ( Ezaier et al, 2022a ; Ezaier et al, 2022b ; Ezaier et al, 2022c ) .…”
Section: Introductionmentioning
confidence: 99%